Ecological groups of xylobiont beetles (Insecta: Coleoptera) in the fresh oak forest of the National Nature Park ‘Gomilshanski Lisy’ (Kharkiv Region, Ukraine) - Bieliavtsev, M. P. (The Kharkiv Entomological Society Gazette, 2022)
In 2019–2021, 204 species of xylobiont beetles from 134 genera of 41 families were found in the fresh oak forest of the National Nature Park ‘Gomilshanski Lisy’. Three species are included into the Red Book of Ukraine, the Red Book of the Kharkiv Region, and the list of the Bern Convention; in addition, 7 more species — in the Red Book of the Kharkiv Region. In terms of the number of species and genera, Staphylinidae dominated, the second place in the number of species was occupied by Curculionidae, but in the number of genera it was inferior to Tenebrionidae and Cerambycidae. In terms of trophic specialization, the leading places are occupied by mycetophages and mixomycetophages (63 species, 31%), saproxylomycetophages and saproxylophages (54 species, 27%), xylophages (34 species, 17%), and predators (29 species, 14%). 1 fig., 3 tabs, 42 refs.